Safety and tolerability of a bevacizumab biosimilar (Effivia®) in adult Mexican patients with cancer: a multicenter, observational, prospective clinical study - Pimentel-Rentería, Alberto Alfonso; Cantú de León, David Francisco; De la Cruz, Eliseo Neftalí; Suárez, David; Segura, Manuel Rodulfo; Núñez, José Gustavo; Delgado-Roche, Livan (Frontiers in Drug Discovery, 2025)
IntroductionSafety of biosimilars is of major relevance for patients and medical community. The aim of this study was to evaluate the safety and tolerability of a bevacizumab biosimilar alongside standard chemotherapy in adult patients with cancer. In addition, the impact on patients’ quality-of-life was assessed.MethodsThis is an observational, multicenter, prospective, phase IV clinical study conducted from April 2022 to April 2024. Adult patients with metastatic cancer were enrolled after informed consent signing. Clinical history, adverse events, and quality of life data were recorded from source documents. Treatment regimens followed the Clinical Practice Guidelines and the Investigator criteria.ResultsAdult patients (n = 82) were included, 65.8% (n = 54) completed the full 6-cycle treatment, while 34.1% (n = 28) meet the criteria for early discontinuation including disease progression (18.3%), voluntary withdrawal or dropout (7.3%), treatment availability or brand switching (4.9%), and serious adverse events (3.7%). The incidence of adverse events was aligned with prior trials, with 97.5% (n = 80) of patients reporting at least one adverse event. The severity of adverse events was mild (86.7%, n = 873), while 11.2% (n = 113) were moderate and 2.1% (n = 22) severe. Five serious adverse events occurred in four patients. The average ECOG score at the end of treatment was similar to the basal score (p > 0.05).ConclusionsThe treatment with the bevacizumab biosimilar Effivia® was considered well tolerated with no additional safety concerns. The average quality-of-life remained stable during treatment. These findings contribute to the growing clinical evidence on the safe use of Effivia® in real-world settings.